Job Burnout : A Study On The Impact Of 6 Job Dimension Towards Job Satisfaction And Propensity To Leave - Lim, Tien Leng (2006)
The purpose of this study is to determine the impact of six job dimension towards the job satisfaction and the likelihood of the sales representatives in the pharmaceutical industries to stay or leave their organizations.